VOICE OF PLAY : Miskitu childrens speech and song on the atlantic coast of nicaragua / Amanda Minks - Minks , Amanda (Arizona : The university of arizona press, 2013)
"Voices of Play "is a study of multilingual play and performance among Miskitu children growing up on Corn Island, part of a multi-ethnic autonomous region on the Atlantic Coast of Nicaragua.
1.Voice of play 2.Historia and Contexts 3.Vocal Play
incluye índice
Col. Educ
Keywords: 1.MULTILINGUAL SPEECH AND SONG 2.PERFORMING 3.INTERCULTURAL VOICE